ANALYSING CHANGES IN SHOOTING PERFORMANCE: ANALYSIS OF PRE AND POST TRAINING SCORES - Pal, Amit; Singh, C. P. Singh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The aim of the present investigation is to examine the effectiveness of a 15-day structured training intervention which comprises stability, precision, and concentration exercises for improving the shooting performance of athletes. The main objective was to evaluate the changes in shooting scores with the help of the intervention. Thirty athletes were randomly recruited in the study and the scores of both the pre and post training were assessed. The experimental group was exposed to the fifteen-day training while the other group received no treatment. The paired t-test signified the effectiveness of the program because shooting performance increased after the training. Even though the scores increased significantly, there was no relationship between pre-test and post-test scores showing that athletes of all skill level got equal benefits from the training. This means that the intervention was generally beneficial no matter the starting point of the students. The study raises questions about the effectiveness of the current training approaches for developing athletic performance and generalises the implications of the study results for training in sports. These results suggest utilization of similar training techniques in the other sports for enhancement of precision and stability. Subsequent studies may examine the durability of such programs and fine-tune their elements to maximize performance results.